Supervisi Akademik dalam Peningkatan KBM Efektif di MA Raden Rahmat Mojowarno Jombang - Ali Mustofa; Sahril Ramadhan (Lembaga Penelitian, Penerbitan dan Pengabdian (LP3M) IAI Al-Urwatul Wutsqo Jombang, 2022)
The existence and development of MA Raden Rahmat Selorejo, Jombang Regency, which is important to note is how to improve the quality of education. Implementation of academic supervision of teacher professionalism in Teaching and Learning Activities. The implementation of academic supervision becomes a benchmark for the development and improvement of the quality of education at MA Raden Rahmat Selorejo. This research is descriptive qualitative research. Implementation of Academic Supervision is also an effort to increase effective teaching and learning activities. Constraints faced during the implementation of Academic Supervision in Increasing Effective Teaching and Learning Activities, namely: the complexity of the managerial tasks of a principal, Lack of preparation from supervised teachers, The element of subjectivity of supervisory teachers is still high, Frequent changes of principals, Facilities and infrastructure that are inadequate limited, Lack of discipline of teachers, and There is still a lack of knowledge of teachers about the effective management of the teaching and learning process.